Clinical Effects of Inadvertent Increased Lipid Infusion in Neonates: Two Case Reports. (8th February 2023) - Hulgan, Christina Marie; Snow, Timothy; Check, Jennifer
Abstract : Background: Utility of total parenteral nutrition (TPN) with an intravenous lipid emulsion (IVLE) component is common in the neonatal intensive care unit; however, there are inherent risks to TPN use. With IVLE administered separate from other TPN components, opportunities exist for additional error and subsequent potential harm. Clinical Findings: We present 2 cases in term infants where IVLE infusions were noted to be inadvertently administered at higher than prescribed rates, prompting concern for lipemia and end-organ damage due to hyperviscosity. Primary Diagnosis: Both infants developed iatrogenic hypertriglyceridemia and hyponatremia. Intervention: Upon recognition of the error, IVLE was immediately discontinued in each case. Triglyceride levels were serially monitored until they reached a normal level. Electrolyte panels and hepatic function panels were also drawn to assess for electrolyte derangements and function. Radiologic studies were performed for evaluation of end-organ effects of hyperviscosity. Outcomes: Triglyceride levels for both infants normalized within 7 hours. Both infants survived to discharge without any known effects related to the inadvertent excessive lipid infusion. Conclusion: It is helpful to perform a root-cause analysis for these types of events; have the exact amount of lipids in the bag needed and no overfill; consider having lipids in 4-hour dosage aliquots; require 2 nurses to verify infusion rates hourly; and educational sessions and unit protocols for any infusion may reduce the risk of administration error.